Layag Talisay Marine Complex necessitating the integration of a localized educational, research, and mercantitle system with the Talisay Fish Port in San Jose, Camarines Sur - Milante, Micah Paula (College of Architecture, University of the Philippines Diliman, 2019)
Layag is a project that intends to lay the development of a Marine Research Complex in Talisay Port, San Jose, Camarines Sur by designing a working system that reinforces and supports municipal fisherfolk and coastal dwellers. In focuses primarily on the integration of a marine research facility with other supplementary spaces to further support adult learning and info-sharing opportunities among the San Jose fisherfolk. This study incorporates an issue-based design as an architectural approach. It aims to benefits municipal fisherfolk who encounter multiple societal issues such as territorial problems, national economic issues like the infamous Train Law, depletion of marines resources due to illegal and irresponsible fishing methods, absence or lack of government support, weather disturbances, privatization of fishing waters and outdated and non-inclusive fisheries law. It also seeks to address current issues on the underutilization of Philippine fish ports. The project includes a design proposal for the following spaces : a small transport terminal, seafood market and dampa, a commercial builing, port and dock, and a marine research station. All of which benefits the target beneficiaries in one way or another.